Comparative Study of the Effects of Education Using VCD and Booklet in Two Different Times on Pre-operative Anxiety - Leila Moemeni; Akram Najaf Yarandi; Hamid Haghani (Iran University of Medical Sciences, 2009)
Background and Aim: Nowadays, CABG is classified among the most common and risky surgeries. Since heart is a vital organ, patients confronting this kind of surgery, experience more anxiety than the patients having other surgeries . The purpose of this study was ti determine the effects of education using VCD and booklet on pre-operative anxiety of CABG candidates in two different times, in Tehran Heart Center-year 2006.   Material and Method: In this clinical trial study, one hundred and twenty 45-65 years old CABG candidates were recruited consecutively and randomly assigned in 4groups, each including 30 patients. All patients completed demographic data sheet and Spiel Berger questionnaire in their admission day and the day of surgery. Every other one patient assigned in two groups of education either by VCD or booklet one day before surgery. After completing patient in two group and one week pause, this procedure was repeated for two other groups of education 6 days before surgery.   Results: sThe findings showed that state and trait anxiety of 4 studied groups reduced after education, when compared with pre-education time. The results of analysis of variance (ANOVA) indicated a statistically significant difference between means of state anxiety before and after education in 4 group (P=0.004). Scheffe test indicated that education using VCD, 6 days before surgery has had the most effect and meanwhile, education using booklet, 6 day before surgery has had the least effect on reducing the state anxiety of participants .   Conclusion: Regarding the results of this study, education using VCD, 6 days before CABG and booklet, one day before CABG has the most effect on reducing pre-operative anxiety .